-9.5n-9.3=-6.82+10.3n-19.6n

Simple and best practice solution for -9.5n-9.3=-6.82+10.3n-19.6n equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -9.5n-9.3=-6.82+10.3n-19.6n equation:



-9.5n-9.3=-6.82+10.3n-19.6n
We move all terms to the left:
-9.5n-9.3-(-6.82+10.3n-19.6n)=0
We add all the numbers together, and all the variables
-9.5n-(-9.3n-6.82)-9.3=0
We get rid of parentheses
-9.5n+9.3n+6.82-9.3=0
We add all the numbers together, and all the variables
-0.2n-2.48=0
We move all terms containing n to the left, all other terms to the right
-0.2n=2.48
n=2.48/-0.2
n=-12+0.08/0.2

See similar equations:

| d-10=-d | | -2.4a+3.4a+9=-2 | | 8(x–4)=3x-7 | | -2(r+6)+3=11r+4(r+4) | | -5x+1=2x+22 | | -5x+1=2x=22 | | 4-4s=-5s | | -12/q=-4 | | 5x+1=2x=22 | | 2(x-20)+4=20 | | 5c-4c=15 | | 18s+15+9=16+16s | | x+1/2=x-2/5 | | 25=z+10 | | q+5=8 | | 6x-16=4x-10 | | 5a+7a=16-4a+2+7a | | -11a-32=3 | | -3((4x+3)+4(6x+1)=43 | | 7(2x+1)-(4x-7)=6 | | 2x-20+4=20 | | 14j+20=16j-20 | | 3x+33=140 | | 3x2–10x+8=(x–)(x–4) | | 2x+4=-2x-1+7 | | −9(a−4)=−5(a−4) | | 3/7=-1/2m | | 0.5(8m-18)=31 | | 2(x+4)+2x=28 | | -5+14r-17=-18+12r | | 9*c/5=-27 | | 6=3+3c |

Equations solver categories